Plantas Cartográficas do Teatro Amazonas - Amorim, Luana Santos de (Brasil, 2022)
The present work aims to present the results of the survey developed by an exploratory research, which was based on data collection through on-site observation of cartographic plants, from the Historical Collection of the Amazonas Theater. Using literature review and technical visit, which highlights the importance of this documentary value of a permanent nature. The survey will enable through qualitative research, the identification of the original plants, their quantification and a documentary control. Through this identification will be performed the ordering of cartographic plants and consequently, suggesting at the end improvements of the packaging for this documentary genre.